The Characterization of Black-streaked Heartwood in Teak: Inter-tree Variation - Ganis Lukmandaru; Tatsuya Ashitani; Koetsu Takahashi (Masyarakat Peneliti Kayu Indonesia, 2014)
The objective of this study was to investigate the variation in the color and chemical characteristics of black-streaked heartwood of teak and explore the relationship of these chemical properties with the degree of blackening. The samples used were outer heartwood parts from 11 trees with black streaks both thin and thick and 7 trees with normal heartwoods for comparison. The colorimetric analysis in CIEL*a*b* system was used to determine the brightness values (L*) of black- streaked heartwood of teak ranging from 40 49 and a thick portion produced appreciably higher average values of extractive contents including n-hexane, ethyl acetate, and total extractive content as well as tectoquinone contents and pH values but lower squalene content compared to those in normal wood. The degree of blackening in the black-streaked heartwood was highly correlated to its extractive contents, especially the ethyl acetate soluble extractive content (r = −0.94) while moderate correlations were measured between the brightness index and tectoquinone content (negative) and squalene (positive). Moreover, no significant difference was found in the ash and individual inorganic elements contents between the group. The increase in pH values was observed to have corresponded with a decrease in brightness (r = -0.75). Therefore, the blackening was assumed to be due to the polymerization of quinones in weakly acidic conditions